132k views
4 votes
What is the solution for 6y+1 = -11

1 Answer

4 votes

I hope this works for you


Simplifying

13 + -6y = 1


Solving

13 + -6y = 1


Solving for variable 'y'.


Move all terms containing y to the left, all other terms to the right.


Add '-13' to each side of the equation.

13 + -13 + -6y = 1 + -13


Combine like terms: 13 + -13 = 0

0 + -6y = 1 + -13

-6y = 1 + -13


Combine like terms: 1 + -13 = -12

-6y = -12


Divide each side by '-6'.

y = 2


Simplifying

y = 2

User Jim Heising
by
5.8k points